Characterization of a novel strain of Tribonema minus demonstrating high biomass productivity in outdoor raceway ponds. (July 2021) - Davis, Aubrey K.; Anderson, Ryan S.; Spierling, Ruth; Leader, Sara; Lesne, Carly; Mahan, Kristina; Lundquist, Tryg; Benemann, John R.; Lane, Todd; Polle, Jürgen E.W.
Highlights: A novel strain of Tribonema minus as a candidate for biofuels feedstock production. Outdoor pond Tribonema minus monoculture outperforms native polyculture. Annual average productivities for reclaimed wastewater cultivation are reported. Low-cost harvesting technology involving screens is applicable for T. minus. Abstract: Photosynthetic algae represent a large, diverse bioresource potential. Yellow-green algae of the genus Tribonema are candidates for production of biofuels and other bioproducts. We report on a filamentous isolate from an outdoor raceway polyculture growing on municipal reclaimed wastewater which we classified as T. minus . Over one year of cultivation in 3.5 m 2 raceway ponds fed by reclaimed municipal wastewater, T. minus cultures were more productive than the native algal polycultures, with annual average productivities of 15.9 ± 0.3 and 13.4 ± 0.4 g/m 2 /day, respectively. The biochemical composition of T. minus biomass grown outdoors was constant year-round, with 28.3 ± 0.4% carbohydrates, 37.6 ± 0.7% proteins, and 6.1 ± 0.3% fatty acids (measured as methyl esters), with up to 4.0% of the valuable omega-3 eicosapentaenoic acid, on an ash-free dry-weight basis. In summary, T. minus was more productive, easier to harvest and produced higher quality biomass than the native polycultures.